2021
DOI: 10.1128/aac.00739-21
|View full text |Cite
|
Sign up to set email alerts
|

Single- and Multiple-Ascending-Dose Study of the Safety, Tolerability, and Pharmacokinetics of the Polymyxin Derivative SPR206

Abstract: Carbapenem-resistant Acinetobacter baumannii and Enterobacterales are identified as urgent threats, and multidrug-resistant (MDR) Pseudomonas aeruginosa and extended-spectrum beta-lactamases (ESBL)-producing pathogens are identified as a serious threat by the Centers for Disease Control and Prevention (CDC). SPR206 is a novel polymyxin derivative with potent in vitro and in vivo activity against A. bauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…Non-clinical toxicology studies in mice, rats and non-human primates have found that SPR206 has a lower risk for kidney toxicity than colistin and polymyxin B ( Brown et al., 2019 ; Zhang et al., 2020 ). A double-blind placebo-controlled single and multiple-ascending-dose study of the safety, tolerability, and pharmacokinetics of SPR206 was conducted on 94 healthy subjects, and SPR206 was generally safe and well-tolerated ( Bruss et al., 2021 ).…”
Section: New Treatments In Developmentmentioning
confidence: 99%
“…Non-clinical toxicology studies in mice, rats and non-human primates have found that SPR206 has a lower risk for kidney toxicity than colistin and polymyxin B ( Brown et al., 2019 ; Zhang et al., 2020 ). A double-blind placebo-controlled single and multiple-ascending-dose study of the safety, tolerability, and pharmacokinetics of SPR206 was conducted on 94 healthy subjects, and SPR206 was generally safe and well-tolerated ( Bruss et al., 2021 ).…”
Section: New Treatments In Developmentmentioning
confidence: 99%
“…There have been efforts to address their pharmacological liabilities with the development of new polymyxin analogs derived from polymyxin B and colistin 8 , 17 22 , 32 34 . While many novel polymyxin B and colistin derivatives have been generated using this approach, very few have entered clinical evaluation 19 , 35 . The polymyxin B analog SPR206 has successfully completed a Phase 1 study of both single- and multipleascending dose cohorts 35 .…”
Section: Discussionmentioning
confidence: 99%
“…While many novel polymyxin B and colistin derivatives have been generated using this approach, very few have entered clinical evaluation 19 , 35 . The polymyxin B analog SPR206 has successfully completed a Phase 1 study of both single- and multipleascending dose cohorts 35 . While no nephrotoxicity was observed at up to 100 mg q8h in the multiple-ascending dose cohort, neurotoxicity at single doses exceeding 200 mg was observed 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has thus a potential broad-spectrum of activity ( Brown et al., 2019 ). Data from a phase I clinical trial were recently published with no evidence of nephrotoxicity and supporting further development of SPR206 ( Bruss et al., 2021 ). Two additional phase I trials ( Figure 4B ) were also completed in December 2021: a bronchoalveolar lavage clinical trial assessing SPR206 penetration into the lungs, and a renal failure study.…”
Section: Polymyxin Derivatives: a New “Old” Class Of Antibioticsmentioning
confidence: 99%